2002
DOI: 10.2135/cropsci2002.1950
|View full text |Cite
|
Sign up to set email alerts
|

Fresh Green Seed Yield and Seed Nutritional Traits of Vegetable Soybean Genotypes

Abstract: et al., 1971). Fresh or frozen vegetable soybean can be cooked just like sweet pea (Pisum sativum L.) or lima Edamame (pronounced eh-dah-MAH-meh) are large-seeded soybean (Phaseolus limensis L.), either stir fried or added bean [Glycine max (L.) Merr.] harvested as green pods at the R6 stage when the seed are approximately 80% matured. The demand to stews and soups. They are nutritious and rich in phyfor edamame as fresh or frozen vegetable is increasing worldwide. tochemicals beneficial to humans. Masuda (199… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
63
3
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(73 citation statements)
references
References 14 publications
6
63
3
1
Order By: Relevance
“…The average content of phytic acid at the R6 stage was lower (1.86 g.100 g -1 ) than that at the R8 (2.61 g.100 g -1 ). Investigating vegetable-type soybean cultivars Rao, Bhagsari and Mohamed (2002) found that the phytic acid content ranged from 1.08 to 1.39 g.100 g -11 , and these values were lower than those observed in this study. The activity of trypsin inhibitor (IT) did not vary with the time of harvest and among the R6 and R8 growth stages.…”
Section: Resultscontrasting
confidence: 93%
See 1 more Smart Citation
“…The average content of phytic acid at the R6 stage was lower (1.86 g.100 g -1 ) than that at the R8 (2.61 g.100 g -1 ). Investigating vegetable-type soybean cultivars Rao, Bhagsari and Mohamed (2002) found that the phytic acid content ranged from 1.08 to 1.39 g.100 g -11 , and these values were lower than those observed in this study. The activity of trypsin inhibitor (IT) did not vary with the time of harvest and among the R6 and R8 growth stages.…”
Section: Resultscontrasting
confidence: 93%
“…The high temperature and low relative humidity at the harvest time of 12:00 AM, compared to that of 8:00 AM and 6:00 PM, probably was not enough to cause variations in the composition of the constituents. The average protein content at the R6 stage was 36.72 g.100 g -1 , and it is in accordance with the result reported by Rao, Bhagsari and Mohamed (2002) for the vegetable-type soybean with contents between 33.32 and 38.60 g.100 g -1 . The average protein content of BRS 267 at the R8 stage, was higher than that at the R6 indicating that the proteins were not fully synthesized at that stage of development.…”
Section: Resultssupporting
confidence: 91%
“…Across varieties, sucrose content of seed from plants in the high tunnel averaged 43 g kg -1 . The protein and oil content of seed in this study were comparable to those reported elsewhere [16,18,19]. While sucrose content were comparable to those reported before [20,21], they are higher than those of vegetable varieties reported in other studies [22].…”
Section: ---------------------supporting
confidence: 90%
“…Although the bone weight increase does not contribute to meat production, the increased bone weight means strong bones. Such a phenomenon suggests the possibility that feeding fermented edamame meal to hens might strengthen the eggshell, because edamame strengthens bones and teeth (Rao et al, 2002). As country roads in the some Asian regions are unpaved, some eggs are broken during transportation.…”
Section: Discussionmentioning
confidence: 99%
“…Nutritionally, edamame is rich in protein (Johnson et al, 1999;Miles et al, 2000), monounsaturated fatty acids (Johnson et al, 1999), vitamin C, vitamin E, dietary fiber (Johnson, 2002), vitamin A, calcium, isoflavones (Masuda, 1991;Rao et al, 2002), as well as calcium, phosphorus, iron, sodium, potassium, vitamin B1, vitamin B2, niacin and ascorbic acid (Miles et al, 2000). Functionally, edamame strengthen bones and teeth, lower cholesterol and prevent cardiovascular disease (Rao et al, 2002).…”
Section: Introductionmentioning
confidence: 99%